Girl wonder : a baseball story in nine innings - Hopkinson, Deborah (Atheneum Books for Young Readers, 2003)
In the early 1900s, Alta Weiss, a young woman who knows from an early age that she loves baseball, finds a way to show that she can play, even though she is a girl.